A CRITICAL ANALYSIS OF LAWS AND JURISPRUDENCE ON SALARIES AND REMUNERATION OF PUBLIC AND STATE OFFICERS IN KENYA - Ochieng, Olayo; Kamau, Lewis (Journal of Public Policy and Administration, 2022)
Purpose: This paper aimed at critically analyzing the laws and jurisprudence on salary and remuneration of public and state officers in Kenya. Methodology: The paper used desk review method. It identified secondary materials related and relevant to study. Particularly, the study journal articles and case laws. Results: The study found that Salaries and Remuneration Commission, as an independent body under the constitution charged with remuneration of public and state officers has experienced lot of interference from other state agencies. At the same time the commission has in some instance acted ultra vires despite the law providing clearly its mandate. Unique contribution to theory, practice and policy: To avoid the court battles as a result of interferences, there is need for the commission to have structural engagement with all public agencies and bodies so as to clarify its mandate. Just as the relationship between the national and county governments is based on the principle of consultation and cooperation, the same can be adopted by the commission to ensure effective and efficient service delivery.